Reservation Wage Rules and Learning Behavior - Sant, Donald T. (The Review of Economics and Statistics, 1977)
T HERE has been much theoretical work done on models of information and search beginning with the work of Stigler (1961, 1962) but there has been little empirical investigation of the implications of these models. With the importance these models have attained in describing macroeconomic phenomena such as the Phillips curve, this empirical work is necessary to guide any potential methods designed to reduce the unemployment rate. This paper examines the time path of wage demands of the unemployed as a test of some of the implications of the search models. Most of the theoretical work has been devoted to analyzing the optimal behavior of individuals who must make choices on the basis of incomplete information and of the equilibrium behavior of markets whose participants behave according to particular search rules. For labor markets it follows that it is not necessarily optimal for an individual to accept the first job offered to him, and thus, the equilibrium position will be characterized by positive unemployment. The search strategy of an unemployed individual usually takes the following form. Search until a wage offer is received that is above some reservation wage, this reservation wage being determined by maximizing expected returns. Since search is a sequential process, the sequence of reservation wages completely describes the behavior of the agents.1 Furthermore, it is derived in most of the theoretical work that this sequence of reservation wages is either constant or monotonically declining. People who remain in the market are willing to accept successively lower wages as time passes.2 This seems to be a paradoxical result about learning, i.e., time always makes one pessimistic. The models in which this monotonicity property is generally derived, do not consider learning as part of the mechanism generating behavior, but for any consistent model of both search and turnover (implicit in the search theories of the Phillips curve) it is required that individuals revise upward their expectations of the wage distribution with the state of the economy. In an economy that is constantly changing, learning should be an important determinant of search. It is hypothesized that when one is permitted or required to learn about the wage distribution through sampling, it seems reasonable to expect that initially pessimistic individuals will revise their wage demands upward before sampling terminates. This paper will argue that the above hypothesis is correct and that the sequence of reservation wages is not monotonically declining. The first part of the paper will present a heuristic formulation of a search and learning model where it can be seen that the sequence of reservation wages depends on the initial expectations of an individual and on the particular sequence of information (including wage offers) that an individual obtains. Although the particular search rule analyzed is not derived from optimization, it should help develop the intuition necessary for believing that reservation wages can and do rise in the course of search. The formulation could be considered as the study of behavior characterized by bounded rationality, but it is mainly presented to motivate the empirical work. The empirical evidence presented supports the hypothesis that a monotonically declining sequence of reservation wages is not an accurate description of actual search behavior of unemployed individuals looking for jobs. The sequence of reservation wages depends heavily on the perceived and actual wage distribution.